2021
DOI: 10.3389/fcell.2021.707572
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression Profiles and Function Predictions for tRFs & tiRNAs in Skin Injury Induced by Ultraviolet Irradiation

Abstract: Ultraviolet (UV) radiation is a major environmental factor contributing skin damage. As UV exposure is inevitable, it is necessary to pay attention to the underlying molecular mechanisms of UV-induced skin damage to develop effective therapies. tRNA-derived stress-induced RNAs (tiRNAs) and tRNA-derived fragments (tRFs) are tRNA-derived small RNAs (tsRNAs) that are a novel class of short, non-coding RNAs. However, the functions behind tRFs & tiRNAs in UV-induced skin injury are not yet clear. Firstly, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…A previous report showed that the ultraviolet irradiation of skin results in the differential expression of several tsRNAs, upregulating tRF-Val-AAC-012, tRF-Pro-AGG-012, tRF-Val-CAC-018, and tRF-Val-AAC-031 and downregulating tRF-Arg-CCT-002, tRF-Trp-TCA-001, tiRNA-Ser-GCT-001, tRF-Gly-CCC-019, tRF-Ala-TGC-001, and tRF-Ala-TGC-002 [ 30 ]. It was speculated that tRF-Gly-CCC-019 targets the ras-related C3 botulinum toxin substrate 1 (Rac1) gene in the WNT signaling pathway and is one of the important players in acute UVB-induced skin injury [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous report showed that the ultraviolet irradiation of skin results in the differential expression of several tsRNAs, upregulating tRF-Val-AAC-012, tRF-Pro-AGG-012, tRF-Val-CAC-018, and tRF-Val-AAC-031 and downregulating tRF-Arg-CCT-002, tRF-Trp-TCA-001, tiRNA-Ser-GCT-001, tRF-Gly-CCC-019, tRF-Ala-TGC-001, and tRF-Ala-TGC-002 [ 30 ]. It was speculated that tRF-Gly-CCC-019 targets the ras-related C3 botulinum toxin substrate 1 (Rac1) gene in the WNT signaling pathway and is one of the important players in acute UVB-induced skin injury [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…ncRNA fragments were shown to be upregulated in response to various stresses, including arsenite treatment and heat shock [ 27 ], nutrition deficiency and hypothermia [ 28 ], tissue hypoxia [ 29 ], and UV radiation [ 30 ]; more information about the role of tiRNAs in stress can be found elsewhere [ 31 ]. Angiogenin (ANG) is one of the endonucleases induced by various cellular stresses that cleave tRNAs into tiRNAs [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is the first study to use predicted miRNAs to identify features that distinguish diseased samples (T2DM or AD) from normal ones, rather than traditional non-biology-based feature selection methods. One novel regulator of post-transcriptional gene expression represents tRNA-derived RNA fragments (tRFs) (8). Results of Zhao et al show that high glucose (HG) treatment induced cardiomyocyte abnormalities, as evidenced by a decrease in cell viability and autophagy activation and increase in cell death and proinflammatory cytokine release.…”
Section: Editorial On the Research Topicmentioning
confidence: 99%
“…RNase angiopoietin cleaves mature tRNA to produce 31–40 nt long RNA strands, which are known as tiRNA. tiRNA can accumulate after oxidative stress, heat shock, ultraviolet radiation, or hypoxia 4 . tRFs are between 14–30 nt and can be further subdivided into tRF-5, tRF-3, and tRF-1 according to their excision positions.…”
Section: Background and Summarymentioning
confidence: 99%